A Certain Investigation of Nanomaterial-Based Li-Ion Batteries for Electrical Vehicles. (31st August 2022) - Sivaramkrishnan, M.; Agenya, R.; Santhi Mary Antony, A.; Baskar, Radhika; Prakash, R. B. R.; Ramya, D.; Sabarimuthu, M.; Golie, Wondalem Misganaw; Brucely, Y.
Abstract : Nowadays, the transports vehicles are required improvement or alternative source for fuel requirement, because of fuel shortage and reducing the global warming. Due to this reason, the electrical vehicle is more concentrated now. The electrical vehicle reduces the carbon emission and reduces the global warming. The main drawback for electrical vehicle is charging time and battery size. To overcome this problem, we use nanomaterial using batteries (like Li-ion battery and Li-based batteries). The nanomaterial particles increase the performance and storage battery capacity and reduce the size of the batteries.